Geochemical characteristics and hydrocarbon generation potential of the first member of Shahejie Formation (E2s1) source rocks in the Dongpu Depression, East China. (27th July 2018) - Lyu, Xueying; Jiang, Youlu; Liu, Jingdong; Xu, Tianwu
Abstract : The Dongpu Depression, containing huge amounts of hydrocarbons, is a typical petroliferous province in the Bohai Bay Basin, east China. As one set of the main source rocks, the first member of Shahejie Formation (E2 s1 ) shows huge exploration potential with approximately 0.83 × 10 8  t resources remaining to be discovered. However, the geochemical characteristics and thermal evolution history of E2 s1 source rocks have still not been determined. In this study, the sedimentary features were firstly analysed based on the geological data. Then the organic matter abundance, kerogen type, and thermal maturity of E2 s1 source rocks in the present day were evaluated according to the Rock‐Eval pyrolysis, micro‐components of kerogen, total organic carbon (TOC), and vitrinite reflectance analysis. Furthermore, the evolution of thermal history and hydrocarbon generation was determined using the PetroMod procedure. The results show that dark mudstones and salt rocks were well developed in E2 s1, which are propitious for organic matter to grow and preserve. E2 s1 source rocks contain abundant organic matter and moderate to good generative source rock potential. E2 s1 source rocks mainly consist of Type II kerogen and have entered early to maturation stage for hydrocarbon generation. Due to the limited buried depth, E2 s1 source rocks only attained lower thermal maturity and generated finite hydrocarbons. The initial rapid subsidence and the second rift after uplift erosion resulted in the higher geo‐temperature at the end of E3 d and the present day. Corresponding to the geo‐temperature evolution, there are two stages of hydrocarbon generation for E2 s1 source rocks: The first stage was in the late E3 d period, and the late stage was from the late Neogene to the present day. Moreover, the hydrocarbon generation rate and quantity of the late stage are much higher than the first stage, indicating the major hydrocarbon generation stage. Due to the limited hydrocarbon generation capacity, oils generated from E2 s1 source rocks are low maturity; thus, it cannot migrate for a long distance and only accumulated around the sag belts.